Projeto e modelagem numérica de armadilha de sedimentos aplicada ao lago do Parque Joaquim Teodoro de Oliveira de Campo Mourão - Paraná - Silva, Sabrina Aguiar da (2020)
Based on the results of studies already carried out in the Rio do Campo basin, this work presents the stages of the development of a solution proposal for the advancement of aggradation of the lake in the Joaquim Teodoro de Oliveira park in Campo Mourão, state of Paraná, a natural process that reaches virtually all water reservoirs and compromises its storage capacity. Initially it was determined that the average flow of the Rio do Campo is 2.21 m³ / s and that the contribution of the sediment load that reaches the lake is approximately 0.18 kg / s. Based on these data, the conception of the initial constructive design of the sediment trap was initiated by means of the desander dimensioning methodology (NBR 12213 (1992)), since a specific and consolidated methodology was not found in the bibliography for the dimensioning of sediment traps. To check the efficiency of the initial project, numerical modeling was used based on computational fluid dynamics (CFD package), a tool that allows the identification of problems and design errors before it is executed, which guarantees reduction of costs, time and optimization of the project, while still in the design phase. The benefits of the tool used were proven by the identification of 4 possibilities for improvement in the initial project: Increased catchment width to eliminate a “dead zone” identified in the first simulation; Changing the location of the sediment discharge gate to take advantage of the direction of the current lines to facilitate the outflow of sediment; Elimination of the internal slope, which proved to be unnecessary after changing the location of the sediment discharge gate and Increasing the diameter of the discharge pipe, to decrease the sediment discharge speed. Therefore, changes in the project were provided and, through it, a new simulation was made. The results of the second simulation proved the benefits of the changes and the goals of the changes could be achieved. Therefore, it can be said that the sediment trap project developed is an effective tool for the control of advancing aggradation of lakes and reservoirs, since it has a minimum efficiency equal to 76% when the entire granulometric distribution of the sediments is considered and 100% in the retention of sediments classified as sand. Finally, it is important to emphasize that one of the premises of this study is its ability to adapt for implantation in other reservoirs, according to the particular characteristics of each location.